Influenza management with new therapies. Issue 3 (May 2020) - O'Sullivan, Shane; Torres, Antoni; Rodriguez, Alejandro; Martin-Loeches, Ignacio
Abstract : Purpose of review: Influenza represents a significant treatment burden to critical care services. A variety of treatment strategies exist, with more and more therapeutic avenues opening up as research progresses. We examined both pharmacological and supportive treatment strategies currently available to see how they might be applied in an ICU setting. Recent findings: Supportive care in Influenza centres around optimizing respiratory failure, particularly through well established and recognized ventilatory strategies. Noninvasive ventilation and high-flow nasal oxygen may have a limited role in selected patients under carefully monitored circumstances. Drug therapy exerts only a modest clinical effect and has been poorly studied in the critically ill, though there is some evidence to support the use of neuraminidase inhibitors (NAI) – particularly oseltamivir – as early as possible in this cohort. Newer agents have failed to demonstrate superiority over NAIs but may be useful options if the patient fails to respond or should resistant influenza strains emerge. Steroid therapy, in the absence of another indication, must be recommended against given the repeated trend towards increased mortality in this group. Summary: Influenza management is an evolving field of significant interest to any critical care provider. Currently, good respiratory supportive care and early enteral oseltamivir are the best supported treatment strategies. Further study in the intensive care setting will be needed before the use of novel agents can be recommended.